SELF REGULATION DALAM PERSPEKTIF HADIST TEMATIK - Ibadurrahman Ibadurrahman; Muhammad Alif (Adisam Publisher, 2026)
Self-control is a fundamental moral value in Islam that is strongly reflected in the hadiths of the Prophet Muhammad (peace be upon him), yet its discussion is often fragmented and treated merely in a normative manner. This article aims to examine the concept of self-control from the perspective of thematic hadith by analyzing its forms, ethical principles, and implications for individual and social life. This study employs a qualitative approach with library research as its primary method. Data were collected from primary hadith sources through thematic exploration using keywords related to self-control, such as patience, emotional regulation, restraint of desires, and moderation. The collected data were analyzed using classification and content interpretation techniques. The findings indicate that self-control in hadith encompasses several key dimensions, including emotional regulation, control of speech, and behavioral restraint in various contexts. The hadiths of the Prophet (peace be upon him) emphasize self-control as a marker of strong faith and moral maturity, while also establishing ethical boundaries such as the prohibition of excessiveness, uncontrolled anger, and submission to unrestrained desires. In terms of implications, self-control plays a significant role in shaping balanced character, maintaining social harmony, and fostering stable interpersonal relationships. Therefore, the concept of self-control within the framework of thematic hadith represents not only a spiritual and normative teaching but also a relevant ethical guideline for addressing contemporary social challenges.